1996
DOI: 10.1063/1.868929
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of jets and vortices in freely evolving, shallow-water turbulence on a sphere

Abstract: Results from a series of simulations of unforced turbulence evolving within a shallow layer of fluid on a rotating sphere are presented. Simulations show that the turbulent evolution in the spherical domain is strongly dependent on numerical and physical conditions. The independent effects of (1) (hyper)dissipation and initial spectrum, (2) rotation rate, and (3) Rossby deformation radius are carefully isolated and studied in detail. In the nondivergent and nonrotating case, an initially turbulent flow evolves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
211
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(244 citation statements)
references
References 38 publications
31
211
2
Order By: Relevance
“…An alternate model of observed cloud level circulation on Jupiter as a surface expression of deep convective columns, oriented parallel to the planetary rotation axis, also exists (Sun, Schubert, & Glatzmeier 1993;Schubert & Zhang 2000). However, only the shallow-layer model has thus far qualitatively reproduced the essential features (bands, zonal winds, persistent spots, and anticyclonic dominance) on all of the giant planets in our solar system using only the observed values of physical parameters (Cho & Polvani 1996a).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternate model of observed cloud level circulation on Jupiter as a surface expression of deep convective columns, oriented parallel to the planetary rotation axis, also exists (Sun, Schubert, & Glatzmeier 1993;Schubert & Zhang 2000). However, only the shallow-layer model has thus far qualitatively reproduced the essential features (bands, zonal winds, persistent spots, and anticyclonic dominance) on all of the giant planets in our solar system using only the observed values of physical parameters (Cho & Polvani 1996a).…”
Section: Modelmentioning
confidence: 99%
“…High-resolution, shallow-layer barotropic models in spherical geometry have been successfully used to model the atmospheric dynamics of the solar system gaseous giant planets (Williams 1978;Cho & Polvani 1996a) as well as stratospheric (stable region) phenomena on the Earth (see, e.g., Juckes & McIntyre 1987). An alternate model of observed cloud level circulation on Jupiter as a surface expression of deep convective columns, oriented parallel to the planetary rotation axis, also exists (Sun, Schubert, & Glatzmeier 1993;Schubert & Zhang 2000).…”
Section: Modelmentioning
confidence: 99%
“…Though not crucial for this paper, we prefer to work on the sphere and not in the ␤-plane approximation, as the sphere can support interesting phenomena not found on the plane (e.g., Cho and Polvani 1996). The absolute vorticity q is given by…”
Section: A Equations Of Motionmentioning
confidence: 99%
“…On rapidly rotating planets, like Jupiter, the wind system outside the Equator is under quasi-geostrophic equilibrium (Ingersoll et al 2004). The theoretical study of the quasi-geostrophic turbulence in a sphere (Rhines 1975) combined with numerical studies with or without forcing and dissipation (Williams, 1978(Williams, , 1979Cho and Polvani, 1996;Scott et al 2007), showed that zonal winds could result from the combination of planetary rotation with the so-called inverse cascade of energy, characteristic of twodimensional turbulence (Vallis 2006). The measurement of turbulent motions (turbulent wind speeds, u', v') is not an easy task since typical values are similar to the standard measurement errors.…”
mentioning
confidence: 99%